2019
DOI: 10.1007/s13205-019-1736-2
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and population structure of watermelon (Citrullus sp.) genotypes

Abstract: Genetic polymorphism amid plant species is a crucial factor for plant improvement and maintaining their biodiversity. Evaluation of genetic diversity amongst plant species is significant to deal with the environmental stress conditions and their effective involvement in the breeding programs. Hence, in present study, an attempt has been made towards the genetic assessment of individual and bulked populations of 25 watermelon genotypes, belonging to Citroides (citron watermelon) and Lanatus (dessert watermelon)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…Moreover, we speci ed the plant height (cm), canopy diameter (cm), number of branches, and stem diameter (mm). We measured the plant height from the soil surface (Van Riper and Owen 1964;Tamkoç 1992) and canopy diameter for the maximum diameter (Acar et al 2019).…”
Section: Morphological Studiesmentioning
confidence: 99%
“…Moreover, we speci ed the plant height (cm), canopy diameter (cm), number of branches, and stem diameter (mm). We measured the plant height from the soil surface (Van Riper and Owen 1964;Tamkoç 1992) and canopy diameter for the maximum diameter (Acar et al 2019).…”
Section: Morphological Studiesmentioning
confidence: 99%
“…Elias (13) found that the largest genetic distance between Charleston Gray and Sugar Baby cultivars was 0.349, and the lowest genetic distance between Crimson Sweet and Sugar Baby was 0.149 after using 12 primers belonging to ISSR technology to show genetic diversity among 21 genotypes belonging to three cultivars, from red watermelon they are Crimson Sweet, Sugar Baby and Charleston Gray. Studied the genetic similarity of 25 genotypes of Citroides (Citron watermelon) and Lanatus (Dessert watermelon) in order to transfer disease resistance from Citroides to Lanatus, which were selected from five different geographical locations using RAPD and ISSR techniques, ISSR had the highest polymorphism of 95.4% , the genotypes of Citron watermelon in Saudi Arabia were similar to those in Turkey, while the highest genetic variance was found between the commercial and local genotypes of Dessert watermelon in Turkey (24). This study was aimed to investigate genetic relation among different watermelon genotypes.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, genome analyses including sequencing, developing molecular markers, transcriptome analyses etc. have gained importance (Sun et al, 2019;Jiang et al, 2019;Pandey et al, 2019). Transposons are also valuable sequences to figure out watermelon genome in detail.…”
Section: Resultsmentioning
confidence: 99%